Roles of Islamic banks in improving financial inclusion of SMES in Indonesia - Adi Saifurrahman (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2022)
The notion of financial inclusion is currently perceived as a vital requirement for sustainable economic development. The concept was viewed initially as pro-poor growth and evolved later as a prerequisite to achieving economic stability and sustainability in the country. One of the critical pillars to promote financial inclusion is the Small and Medium Enterprises (SMEs) sector. In Indonesia particularly, SMEs are regarded as a critical engine for job creation and essential contributors to the country’s Gross Domestic Product (GDP). Therefore, the inclusion of this potential sector into the Islamic financial services is exceptionally imperative to alleviate poverty, reduce unemployment, and minimise income disparity in the country. The primary objective of this study was to identify and explore the role of Indonesian Islamic banking institutions in realising financial inclusion by addressing the needs of Indonesian SMEs in the context of their services, analysing the issues and challenges that inhibit the institutions’ ability to support the SMEs in gaining access to finance, and elucidate the endeavours of the Islamic banking institution to assist and reach over the SME segment through the regulatory, supply-side, demand-side and financial literacy determinants. This study incorporated the institutional theory as its theoretical premise and used qualitative methodology by adopting a multi-case study research strategy on the Indonesian Islamic banks (as the supply-side) in serving the needs of SMEs as well as the SME industry in its diverse sectors (as the demand-side). The research data were analysed by applying a content, narrative and discourse analysis to investigate the study’s results and integrate the triangulation methods by comparing the three elements consisting of primary data, secondary data and theoretical proposition. The findings of this study implied that the Islamic banks present a substantial role in improving the financial inclusion of the SME segment through diverse strategies and approaches intended to facilitate its growth. Nevertheless, several issues and challenges still hamper the achievement of SME Islamic financial inclusion in Indonesia. Lack of incentives, Profit and Loss Sharing (PLS) implementation challenges, credit risk assessment gaps, high-price perception, issues of government programmes, and poor financial literacy of SMEs became the primary factors that negatively affect the achievement of Islamic financial inclusion for SMEs. Subsequently, the study also disclosed the SME entrepreneurs’ expectations and perceptions towards the Islamic banks’ products and services, denoting the opportunities that should be taken into consideration by the Indonesian Islamic banks. Additionally, the study is also expected to contribute to the empirical and theoretical analysis involving financial inclusion, Islamic banks, SMEs, and institutional theory aspects.